2016
DOI: 10.1038/srep23192
|View full text |Cite
|
Sign up to set email alerts
|

Range wide molecular data and niche modeling revealed the Pleistocene history of a global invader (Halyomorpha halys)

Abstract: Invasive species’ Pleistocene history contains much information on its present population structure, dispersability and adaptability. In this study, the Pleistocene history of a global invasive pest (Brown Marmorated Stink Bug BMSB, Halyomorpha halys) was unveiled using the coupled approach of phylogeography and ecological niche modelling. Rangewide molecular data suggests that the Taiwan and other native populations had diverged in mid-Pleistocene. In mainland China, the native BMSB did not experience populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
2
43
1
Order By: Relevance
“…Mountainous areas also potentially harboured many refugial populations in the ice age, which led to the formation of new lineages/taxa and contributed to a higher genetic diversity (Jiang et al ., ; Ye et al ., ). Previous studies of East Asian insects, including Apocheima cinerarius (Lepidoptera: Geometridae) (Liu et al ., ) and Halyomorpha halys (Hemiptera: Pentatomidae) (Zhu et al ., ), have confirmed that Pleistocene climate change had an effect on the distribution and demography these species, which survived in refugia during glacial periods, experienced demographic expansion after the ice age and, eventually, formed their current population structures due to the complex local topography.…”
Section: Introductionmentioning
confidence: 61%
“…Mountainous areas also potentially harboured many refugial populations in the ice age, which led to the formation of new lineages/taxa and contributed to a higher genetic diversity (Jiang et al ., ; Ye et al ., ). Previous studies of East Asian insects, including Apocheima cinerarius (Lepidoptera: Geometridae) (Liu et al ., ) and Halyomorpha halys (Hemiptera: Pentatomidae) (Zhu et al ., ), have confirmed that Pleistocene climate change had an effect on the distribution and demography these species, which survived in refugia during glacial periods, experienced demographic expansion after the ice age and, eventually, formed their current population structures due to the complex local topography.…”
Section: Introductionmentioning
confidence: 61%
“…A large global distribution of BMSB is projected from climate-matching models (161) and/or inference of the species Pleistocene history from molecular data (162). The introduction pathways and propagule size of an invading population may impact species ecology, including its fitness.…”
Section: Origin Spread and Impact (Including Agriculture And Nuisance)mentioning
confidence: 99%
“…For example, in Europe, many studies have shown how the persistence of populations in separate glacial refugia (e.g., the Iberian, Italian, and Balkan peninsulas, the Caucasus region, North Africa, and microrefugia in the Alps) during the Quaternary climatic oscillations promoted genetic diversity in contemporary populations (Andersen, Havill, Caccone, & Elkinton, ; Habel, Lens, Rodder, & Schmitt, ; Huck, Buedel, & Schmitt, ; Niedzialkowska et al, ; von Reumont, Struwe, Schwarzer, & Misof, ; Rofes et al, ; Schmitt, ; Schmitt & Müller, ; Sim, Hall, Jex, Hegel, & Coltman, ; Stolting et al, ; Torroni et al, ). For outbreaking species, reconstructing the biogeographical history of the species can help to determine the factors that might be promoting their outbreak (e.g., Moyal et al, ; Song et al, ; Zhu et al, ).…”
Section: Introductionmentioning
confidence: 99%